Does income converge among eu member countries following the post-war period? Evidence from the PANKPSS test - Ozcan, Burcu (Institute foe Economic Forecasting, 2014)
In this study, we examine both stochastic and deterministic convergence in the logarithm of the relative per capita income of eighteen EU countries. The panel stationary test developed by Carrion-i Silvestre et al. (2005) is employed over the period 1950-2010. The univariate results attained from the stochastic convergence test provide that convergence does hold for sixteen countries except for Bulgaria and Ireland. In addition, the findings of the deterministic convergence test render the evidence favourable to convergence in sixteen EU countries as well, except for Austria and Greece. In other words, the individual results from panel stationarity tests are mostly in support of income convergence among EU members. Furthermore, both types of convergence appear to hold for the entire EU panel set. Therefore, shocks to relative per capita income levels of EU countries appear to be temporary. © 2014 Institute foe Economic Forecasting. All rights reserved.
Keywords: Catch-up; Deterministic convergence; Panel stationarity test; Stochastic convergence; Structural breaks